Optimum conditions of ultrasound‐assisted extraction and pharmacological activity study for phenolic compounds of the alga Chondrus ocellatus. Issue 3 (28th January 2022) - Zhu, Yuexia; Chen, Weiqi; Kong, Li; Zhou, Bingxue; Hua, Yue; Han, Yue; Li, Jiaojiao; Ji, Jing; Fu, Mian; Liu, Weiwei; Qin, Kunming; Dong, Zibo; et al.
Abstract: Chondrus ocellatus is a kind of red algae and shows diverse pharmacological activities. This article planned to extract polyphenols and study their pharmacological activities. The extraction conditions were optimized utilizing response surface methodology. Antioxidant activities, α‐amylase, and α‐glucosidase inhibitory activity were tested. The consequences revealed that optimal extraction was obtained with an ethanol concentration of 61%, an extraction time of 41 min, and an extraction temperature of 60°C. The extracts inhibited ABTS and DPPH with 43.48%–53.50% and 13.11%–25.77%, respectively. For H2 O2, the inhibition was 18.4–85.6 U/ml. The IC50 values were 16.92 ± 2.31 mg/ml (anti‐α‐glycosidase) and 375.3 ± 3.47 mg/ml (anti‐α‐glucosidase). The extracts showed competitive and mixed inhibition against α‐amylase and α‐glucosidase, respectively. This study provided preliminary data for the anti‐type 2 diabetes treatment of phenolic compounds from C. ocellatus . Practical applications: The algae were not only a marine plants but also a medicine. This study demonstrated that polyphenol extract of the alga Chondrus ocellatus is a potential drug for the treatment of type 2 diabetes. Further study is necessary to evaluate the effect of polyphenol extracts in animal models and establish their beneficial activity in humans.